Characteristics of Malignant Eyelid Basal Cell Carcinoma in Dr. Mohammad Hoesin General Hospital: A Retrospective Study - Mutia Arnisa Putri; Ibrahim (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Incidence rates of skin cancer have risen significantly over the last two decades. Most tumors develop in sun-exposed areas of the head and neck. Basal cell carcinoma (BCC) rarely metastasizes but can cause significant morbidity and death due to direct spread to the orbit, head, and neck and frequent recurrence. In addition, approximately 40% of BCC patients have other lesions after 5 years. Although there has been a lot of epidemiological data regarding the characteristics of BCC in developed countries, reports of BCC in Asia, especially in Southern Sumatra, are still at a minimum rate. Methods: This study retrospectively reviewed the medical records specific to periocular BCC. Data were collected from the patient register book recorded from January 2021 to May 2022. The clinical characteristics of patients with BCC, such as gender and age, clinicopathological findings of BCC lesions, and BCC management, were reviewed retrospectively. This study aims to determine the epidemiological profile of the malignant eyelid BCC patient, the BCC lesion characteristics, and the management of BCC cases at Mohammad Hoesin General Hospital Palembang. Results: From 16 BCC patients recruited for this study, most of them were 51–60 years old and 71–80 years old, each with 5 patients (31.3%). The female preponderance of 56.3%. Occulus dextra (56.3%), lower eyelid (62.5%), T1 (87.5%), nodular BCC (75,0%), and primary lesion (75,0%) were the most side, periocular site, size, histopathological subtype and recurrence, respectively. Most therapy done is excision (93,8%), while the leading reconstructive technique was Tenzel’s flap (50,0%). Conclusion: There is a slight preponderance of females as BCC patients. BCC is commonly found in elderly people. The lower eyelid and right side are the most frequent anatomical locations. Nodular is the most common histological subtype. In addition, lesions often present in T1 size and primary lesions. Lastly, the treatment is mainly surgical (excision), with Tenzel's flap as the most used reconstruction technique option.